Impact of mothers' IPV-PTSD on their capacity to predict their child's emotional comprehension and its relationship to their child's psychopathology. Issue 1 (31st December 2022) - Pointet Perizzolo, V. C.; Glaus, J.; Stein, C. R.; Willheim, E.; Vital, M.; Arnautovic, E.; Kaleka, K.; Rusconi Serpa, S.; Pons, F.; Moser, Dominik A.; Schechter, D. S.
ABSTRACT: Background: Previous studies demonstrated that when the violence-exposed child becomes a mother and interacts with her own child during early sensitive periods for social-emotional development, she may have difficulties providing sensitive responsiveness to the child's emotional communication. Such difficulties place the child's development of emotional comprehension (EC) and related self-regulation at risk. The aim of this study was to examine how mothers' interpersonal violence-related posttraumatic disorder (IPV-PTSD) would affect their children's EC and their own ability to predict their children's EC. We also investigated how mothers' predictive ability would correlate with child psychopathology. Methods: Sixty-one mother–child dyads (36 with IPV-PTSD) participated in this study. Children's (mean age = 7.0 years, SD = 1.1) EC was assessed with the Test of Emotion Comprehension (child TEC) and their psychopathology as reported by the mother was assessed with the Child Behaviour Checklist (CBCL) and as evaluated by a clinician using selected modules of the Kiddie Schedule for Affective Disorders and Schizophrenia (K-SADS). Mothers were measured for IPV-PTSD with the Clinician Administered PTSD Scale (CAPS) and for their capacity to predict their child's emotional comprehension (mother-responding-as-child TEC; mTEC). Results: We found no significant between-group differences in children's level of EC. Maternal PTSD was associated with lower scores on the mTEC, however. Reduced maternal scores on the mTEC were significantly associated with maternal report of increased aggressive child behaviour and with depression symptoms on the K-SADS. Further, scores on the mTEC interacted with maternal report of child aggression on child oppositional defiant disorder (ODD) symptoms on the K-SADS. Conclusion: These findings support that improving maternal emotional comprehension may help reduce child risk for psychiatric morbidity in this population. HIGHLIGHTS: Maternal estimation of children's responses (mTEC) on the test emotion comprehension is reduced among mothers with PTSD. Low mTEC associated with high maternal estimation of child aggression. Low mTEC associated with more child depression symptoms on child/clinician report.